Ken Yeager at lectern - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Ken Yeager standing at a lectern with his back to the camera. He is speaking outside to a group of people in front of San Jose City Hall on West Mission Street. Yeager was the first openly gay member of the San Jose City Council.